MAGNETOSOMES SYNTHESIZED BY MAGNETOTACTIC BACTERIA STENOTROPHOMONAS SPP. STRAIN RP-8 FOR MAGNETIC HYPERTHERMIA - PATIL R.N,; KARANDE V. A,; GHOSH S.J,; PAWAR S.H, (International Journal of Pharma and Bio Sciences, 2014)
Magnetosomes isolated from magnetotactic bacteria Stenotrophomonas spp. strain RP-8 was tested for magnetic fluid hyperthermia. Strain RP-8 cultivated in optimized magnetospirillum growth medium with microaerophilic condition under permanent magnetic field and magnetosomes were extracted by sonication. Transmission electron microscopic observation reveals the presence of magnetosomes whereas alternative gradient magnetometer (AGM) analyzed the magnetic measurement. The maximum Specific Absorption Rate (SAR) of magnetosomes is shown as 337.30 W/g at 502 Oe magnetic fields. In the present investigation, the magnetic properties and heating efficiency of magnetosomes extracted from strain RP-8 was applied for magnetic fluid hyperthermia.